Laubieriopsis petersenae n. sp. and L. cf. cabiochi (Amoureux, 1982) (Polychaeta: Fauveliopsidae) from dredge disposal sites off Honolulu, Hawaii - Magalhães, Wagner F.; Bailey-Brock, Julie H.; Rizzo, Alexandra E. (Zootaxa, 2014)
Fauveliopsid polychaetes have been collected at dredge disposal sites off Honolulu from 397–507 m depth. We report and describe the first Pacific record of Laubieriopsis cf. cabiochi (Amoureux, 1982), originally described from the North Atlantic. A new species, Laubieriopsis petersenae, n. sp. is described as being the species in the genus with the lowest number of body segments (15). Other distinctive features are the presence of bidentate aciculars on thoracic chaetigers, and unpaired genital papilla present on the right side of chaetiger 6/7. The new species is most similar to the L. brevis complex from the Atlantic and L. hartmanae and L. brevis japonica from the Pacific Ocean, but differs on the combination of the characters cited above. We provide an emended diagnosis for this genus to include the ultrastructure of the acicular with rows of spines, and a key to all described species.